2011
DOI: 10.1016/j.yjmcc.2010.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human embryonic stem cell-derived cardiomyocyte growth: A testbed for studying human cardiac hypertrophy?

Abstract: Human embryonic stem cell-derived cardiomyocytes (hESC-CM) are being developed for tissue repair and as a model system for cardiac physiology and pathophysiology. However, the signaling requirements of their growth have not yet been fully characterized. We showed that hESC-CM retain their capacity for increase in size in long-term culture. Exposing hESC-CM to hypertrophic stimuli such as equiaxial cyclic stretch, angiotensin II, and phenylephrine (PE) increased cell size and volume, percentage of hESC-CM with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 35 publications
7
123
0
2
Order By: Relevance
“…An a-adrenoceptor agonist PE (100 lM) was used to induce cardiomyocyte hypertrophy [3]. The hypertrophy was assessed by four cardiomyocyte hypertrophic indexes, including cell size enlargement [31], sarcomere organization [27], and expression of cardiac hypertrophic markers ANF and ACTA1 [27,32].…”
Section: Increased Expression Of Orai1 During Hes2-cm Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation
“…An a-adrenoceptor agonist PE (100 lM) was used to induce cardiomyocyte hypertrophy [3]. The hypertrophy was assessed by four cardiomyocyte hypertrophic indexes, including cell size enlargement [31], sarcomere organization [27], and expression of cardiac hypertrophic markers ANF and ACTA1 [27,32].…”
Section: Increased Expression Of Orai1 During Hes2-cm Hypertrophymentioning
confidence: 99%
“…Recently, human embryonic stem cells (hESCs) and humaninduced pluripotent stem cells (hiPSCs) are used to generate cardiomyocytes. These hESC-or hiPSC-derived cardiomyocytes are suggested to have many of the properties of authentic cardiomyocytes [2,3]. hESC-and hiPSC-derived cardiomyocytes are relatively immature.…”
Section: Introductionmentioning
confidence: 99%
“…Use of hiPSC-CMs for assessing apoptotic, proliferative and hypertrophic activity is much less explored, but assays are being developed using both live and fixed cells (Földes et al, 2011). Proliferative activity, as detected by increase in cell number, Ki67 + , phosphorylation of histone H3 and relative distribution of cells in G2 M -1 and G1/G0 phases of cell cycle, can be set up for automated analysis.…”
Section: Screening Of Non-cardiac Drugsmentioning
confidence: 99%
“…Proliferative activity, as detected by increase in cell number, Ki67 + , phosphorylation of histone H3 and relative distribution of cells in G2 M -1 and G1/G0 phases of cell cycle, can be set up for automated analysis. Assays for hypertrophic changes such as increases in cell size, protein content, sarcomere assembly and ANP/BNP have also been automated and may be useful markers of long-term cardiac toxicity (Földes et al, 2011).…”
Section: Screening Of Non-cardiac Drugsmentioning
confidence: 99%
“…This immaturity is reflected by low maximal diastolic potentials because of insufficient inwardly rectifying K ϩ current and slow upstroke velocities (79,(103)(104). Evidence suggests that prolonged culturing (27,54), addition of nonmyocytes (45), and the 3-D format in EHT promote some aspects of maturation. Zhu et al (104) demonstrated that the differentiation in the presence of neuregulin increased the percentage of mature cardiomyocytes with slower firing rate, increased upstroke velocities, and more negative maximum diastolic potential.…”
Section: Tissue Engineering To Model (Human) Heart Tissue Functionmentioning
confidence: 99%